Physical Properties and Consumer Acceptance of White Bread with The Substitution of Coconut Dregs and Avocado Seed Flour - Winda Dwi Oktarini; Delsi Anjarwati; Ari Setiawan; Nabilla Dhiya Ulhaq; Desiana Nuriza Putri (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
Analysis of the relationship between physical properties and consumer acceptance, which is commonly influenced by sensory properties is crucial in delivering a high-quality food product. Therefore, this study aimed to analyze the effect of physical properties, including hardness, adhesiveness, dough expansion, specific volume, color intensity (L*, a*, b*, and °hue), browning index, and analysis of consumer acceptance by employing Partial Least Squares (PLS) regression. The analysis focused on high-fiber white bread made by substituting coconut dregs and avocado seed flour with different ratios, denoted as P0 (control), P1 (90% wheat flour: 5% coconut dregs flour: 5% avocado seed flour), P2 (85% wheat flour: 10% coconut dregs flour: 5% avocado seed flour), P3 (80% wheat flour: 15% coconut dregs flour: 5% avocado seed flour), P4 (75% wheat flour: 20% coconut dregs flour: 5% avocado seed flour), and P5 (70% wheat flour: 25% coconut dregs flour: 5% avocado seed flour). The results showed that consumer preferences had a positive correlation with the physical properties of white bread, including hardness, adhesiveness, dough expansion, specific volume, as well as colors L*, and °hue, while, a*, b*, and had a negative correlation with the browning index. The circular correlation analysis between physical properties and consumer acceptance indicated that the substitution of 25% coconut dregs flour and 5% avocado seed flour in white bread was accepted by consumers.